A novel endoscopic assessment of the gastroesophageal junction for the prediction of gastroesophageal reflux disease: a pilot study - Inoue, Haruhiro; Fujiyoshi, Yusuke; Abad, Mary Raina Angeli; Rodriguez de Santiago, Enrique; Sumi, Kazuya; Iwaya, Yugo; Ikeda, Haruo; Onimaru, Manabu; Shimamura, Yuto (Endoscopy International Open, 2019)
Background and aim Hiatal hernia and lower esophageal sphincter (LES) dysfunction play major roles in gastroesophageal reflux disease (GERD) pathogenesis. We developed a novel endoscopic assessment to evaluate the gastroesophageal junction (GEJ). This study aims to evaluate the feasibility of this method for the diagnostic prediction of GERD.Methods A retrospective analysis of patients with GERD symptoms who underwent gastroscopy and esophageal pH-impedance monitoring was conducted. The novel assessment evaluated the following in retroflex view: 1) Cardiac Opening (CO): diameter of the opening of the cardia, 2) Sliding Hernia (SH): length from the diaphragmatic crus to the squamocolumnar junction, 3) Scope Holding Time% (SHT%): the percentage of time that the Scope Holding Sign (SHS) was observed out of 30 seconds. The SHS is defined as the lower esophagus holding the endoscope under excessive insufflation. The results of this assessment and that of pH-impedance monitoring were compared.Results In total, 61 patients (mean age ± SD, 54.1 ± 16.4 years, 32 males) were enrolled. CO and SH were significantly correlated with acid exposure time (AET) (ρ = 0.36, P = 0.005, and ρ = 0.36, P = 0.004). The optimal cutoff of CO for AET > 6 % was 3 cm (Sensitivity = 72.4 %, Specificity = 46.9 %, AUC = 0.64) and that of SH was 2 cm (Sensitivity = 55.2 %, Specificity = 75.0 %, AUC = 0.70). When the population was stratified according to this cutoff, patients with CO > 3 cm and those with SH > 2 cm presented higher AET (15.1 vs 4.1 %, P = 0.037, and 23.0 vs 3.6 %, P = 0.026). Optimal cutoff of SHT% for the number of all reflux episodes > 80 was 75 % (Sensitivity = 81.8 %, Specificity = 54.6%, AUC = 0.67). Patients with SHT% < 75 % presented a higher number of all reflux episodes (88 vs 65, P = 0.014). Sensitivity, specificity, and accuracy of SHT% < 75 % for all reflux episodes > 80 were 81.8 % (95 %CI: 67.7 – 91.8), 54.5% (95 %CI: 40.4 – 64.5), and 68.2 % (95 %CI: 54.0 – 78.1).Conclusion This novel endoscopic assessment of GEJ significantly predicted the presence of GERD and merits further testing in future studies.